Health literacy of nursing students and its effective factors. Issue 3 (17th April 2019) - Ozen, Nurten; Bal Ozkaptan, Bilge; Coskun, Sabahat; Terzioglu, Fusun
Abstract: Background: The insufficiency of health literacy negatively affects the national economy as it leads to increased health service expenditure. It is very important for individuals to have accurate health‐related information to reduce these negative effects. Aim: The aim of the study is to examine the health literacy of nursing students and its effective factors. Methods: This descriptive study was carried out with students from the nursing department of a vocational school of health sciences between September and October 2018 in Turkey. A semi‐structured questionnaire regarding the descriptive features of the participants and the European Health Literacy Scale were used for data collection. Results: The study included 283 nursing students; 29.3% had a problematic‐limited health literacy level. The study found a statically significant difference between student year, high school graduation and family's income level and the total mean score of the HLS‐EU scale. Conclusion: The subject of health literacy should be integrated into the educational program of nursing students. The nurses are the most important workforce in health services, and awareness about this subject should be raised.